AN APPROACH TO SOFT FUNCTIONS - Aras, Cigdem Gunduz; Sonmez, Ayse; Cakalli, Huseyin (Univ Prishtines, 2017)
In this paper, using a more appreciate definition of a soft point, i.e. a soft point is a soft set (F, E) such that for the element e is an element of E, F(e) = {x} and F(e ') = (empty set) for all e ' is an element of E - {e}, we present a new approach to soft functions in a interesting way, and introduce the concepts of soft continuous, soft open, soft closed, and soft homeomorfic functions in a very different way from the source existing in the literature. In the investigation we prove theorems related to these concepts and provide with examples, and counterexamples.
Keywords: soft topology; soft sets; soft continuity